Solubility Parameters of Permanent Gases - Yizhak Marcus (Journal of Chemistry)
The solubility parameters, δH(Tb), of nonreactive permanent gases at their boiling points Tb (<290 K) are calculated from individually discussed values of their molar enthalpies of vaporization and densities obtained from the literature. These values are tabulated and where available the coefficients of the temperature dependence expression δH(T) are also tabulated. The trends noted in the δH(Tb) values are dealt with and the values are compared with those reported in the literature and derived from the solubilities of the gases in various solvents. The δH(Tb) values are shown to correlate linearly with the depths of the potential wells (attractive interaction energies, ε/kB) for binary collisions of the gaseous molecules and with the surface tensions, σ(Tb), of the liquefied gases.